Active mobility and the 2030 Sustainable Development Goals, with a focus on education for health and the environment: An analysis from the characteristics of the individual, the environment and the task (Research, Society and Development, 2021)
The purpose of this article is to verify active mobility and the 2030 Sustainable Development Goals, focusing on education for health and the environment, based on the characteristics of the individual, the environment and the task. The study was of the descriptive documentary type. The document entitled “Transforming Our World: The 2030 Agenda for Sustainable Development” (United Nations [UN], 2015) was analyzed. Analysis categories: health, education and climate change. The categories were analyzed based on the characteristics of the individual, the environment and the task, and their interconnections, proposed by the Newel Model (Newell & Jordan, 2007; Newell, 1986). The results indicate that active mobility presents itself as a way of promoting health and reducing the amount of polluting gases in the environment. The educational learning environment creates opportunities, instruction and encouragement for active mobility to be carried out in a healthy way and in a sustainable environment. It was concluded that active mobility can be developed in the formal and non-formal educational environment, in specific activities, as well as through long-term maintenance interventions, in addition to expanding the contexts of the actions that are necessary, aiming at greater effectiveness in health and the environment.